ANALYTICAL OBSERVATION OF INSTRUCTIONAL PROCESS IN SOCIAL STUDIES IN UPPER BASIC SCHOOLS IN BAYELSA STATE OF NIGERIA - Amatari, Veronica Odiri (PUPIL: International Journal of Teaching, Education and Learning, 2020)
Classroom communication is a vital ingredient in every instructional learning process within the school environment. The quality and quantity of teacher-pupil interaction is a critical dimension of effective classroom teaching. This prompted the development of a Classroom Interaction Sheet (CIS) for an analytical observation of behavioral activities that are predominant in a teaching /learning process in Social Studies. The Classroom Interaction Sheet observed 3 categories of behavior namely, teachers’ activities, students’ activities, and others. The frequency of occurrence for each activity was observed for thirty-two instructional lessons. The inter-rater reliability estimated for CIS is 0.60. Data were analyzed with frequency/percentage and independent t-test statistical techniques. Findings show teachers’ activities have the highest occurrence of 54%, followed by students’ activities of 43%. Furthermore, students’ behavioral activities such as responding to questions; listening: and hand up to respond got the highest scores of 12%, 13%, and 12% respectively. Teachers’behavioural activities that occurred most are: explaining (16%); standing in front of the class (14%); and demonstrating with hands (13%). Gender of the teacher and school type did not significantly affect classroom interaction (i.e. t(30)=0.053,p>0.05 and t(30)=0.512,p>0.05). It is recommended that teachers’ behavioral activities such as praising and encouraging pupils’ efforts; and giving assignment which scored low should be improved on. Conclusively, the teacher’s dominance in classroom interaction is sustained in this study.